Belowground interactions with aboveground consequences: Invasive earthworms and arbuscular mycorrhizal fungi. Issue 3 (March 2016) - Paudel, Shishir; Longcore, Travis; MacDonald, Beau; McCormick, Melissa K.; Szlavecz, Katalin; Wilson, Gail W. T.; Loss, Scott R.
Abstract: A mounting body of research suggests that invasive nonnative earthworms substantially alter microbial communities, including arbuscular mycorrhizal fungi (AMF). These changes to AMF can cascade to affect plant communities and vertebrate populations. Despite these research advances, relatively little is known about (1) the mechanisms behind earthworms' effects on AMF and (2) the factors that determine the outcomes of earthworm–AMF interactions (i.e., whether AMF abundance is increased or decreased and subsequent effects on plants). We predict that AMF‐mediated effects of nonnative earthworms on ecosystems are nearly universal because (1) AMF are important components of most terrestrial ecosystems, (2) nonnative earthworms have become established in nearly every type of terrestrial ecosystem, and (3) nonnative earthworms, due to their burrowing and feeding behavior, greatly affect AMF with potentially profound concomitant effects on plant communities. We highlight the multiple direct and indirect effects of nonnative earthworms on plants and review what is currently known about the interaction between earthworms and AMF. We also illustrate how the effects of nonnative earthworms on plant–AMF mutualisms can alter the structure and stability of aboveground plant communities, as well as the vertebrate communities relying on these habitats. Integrative studies that assess the interactive effects of earthworms and AMF can provide new insights into the role that belowground ecosystem engineers play in altering aboveground ecological processes. Understanding these processes may improve our ability to predict the structure of plant and animal communities in earthworm‐invaded regions and to develop management strategies that limit the numerous undesired impacts of earthworms.